Does adding variceal status to the Child–Turcotte–Pugh score improve its performance in predicting mortality in cirrhosis?. Issue 38 (September 2016) - Fan, Xiaoli; Wen, Maoyao; Shen, Yi; Wang, Wanqin; Yang, Xiaoxue; Yang, Li
Abstract : Abstract: The Child–Turcotte–Pugh (CTP) score is widely used worldwide to predict outcomes across a broad spectrum of liver diseases, mainly cirrhosis. Portal hypertension and variceal bleed are significant causes of morbidity and mortality in cirrhotic patients, although the variceal status is not incorporated into the classical CTP score. We sought to determine whether the inclusion of variceal status, specifically the Child–Turcotte–Pugh–Kumar (CTPK) score, would improve the utility of the classical CTP score to predict the clinical outcomes of cirrhotic patients in a single but high-volume center in China. We retrospectively analyzed the records of 253 patients from January 1, 2014 to December 31, 2014 and performed follow-up for at least 12 months. The CTPK score and the CTP score were obtained as soon as possible after the patient's admission. Telephone follow-up was performed to assess survival situations. At 3 and 12 months, the cumulative number of deaths was 9.1% (n = 23) and 13.8% (n = 35), respectively. In the multivariate Cox proportional hazards models, the CTPK score was independently associated with death within 3 and 12 months after adjusting for potential confounders. The predictive ability related to the 2 scores was evaluated by the area under the receiver operating characteristic curve (AUC-ROC) respectively. At 3 months of enrollment, the AUCs of CTPK and CTP were 0.814 and 0.838, respectively. At 12 months of enrollment, the AUCs of CTPK and CTP were 0.825 and 0.840, respectively. No significant difference between time points was observed. Both the CTPK score and the CTP score displayed prognostic value in cirrhotic patients, as the Kaplan–Meier analysis showed that the CTPK score could clearly discriminate patients in the intermediate term ( P < 0.001). The CTPK score provides reliable prediction of mortality in Chinese cirrhotic patients for both short-term and medium-term prognoses, although it is not superior to the CTP score. Therefore, the CTP score remains an excellent tool for outcome prediction in patients with cirrhosis, and greater attention to variceal status may be in veins, even for patients with a history of variceal bleed or medium/large varices.